Motivational Factors Affecting Emirati English Learners - Watt, Rachael (2024)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Rachael Watt entitled, “Motivational Factors Affecting Emirati English Learners”, submitted in November 2024. Thesis advisor is Dr. Maria Eleftheriou and thesis co-advisor is Dr. Ozgur Parlak. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).